2017
DOI: 10.1093/annonc/mdx683
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral immunotherapy: using the tumor as the remedy

Abstract: Immune checkpoint-targeted monoclonal antibodies directed at Programmed Death Receptor 1 (PD-1), Programmed Death Ligand 1 (PD-L1) and Cytotoxic T-Lymphocyte Associated Protein 4 (CTLA-4) are currently revolutionizing the prognosis of many cancers. By blocking co-inhibitory receptors expressed by antitumor T cells, these antibodies can break the immune tolerance against tumor cells and allow the generation of durable cancer immunity. Benefits in overall survival over conventional therapies have been demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
275
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(283 citation statements)
references
References 59 publications
6
275
0
2
Order By: Relevance
“…Direct injection of various biological and chemical agents into tumors as an approach for cancer therapy has a longstanding history with William B. Coley’s efforts in the late 19 th century (Aznar et al, 2017; Marabelle et al, 2017). These agents include but are not limited to TLRs, RIG-I-like receptor (RLR) agonists, STING pathway modulators (Corrales et al, 2016; Li et al, 2017), and oncolytic viruses (Lawler et al, 2017).…”
Section: The Principles To Combine Other Therapeutics With Anti-pd Thmentioning
confidence: 99%
“…Direct injection of various biological and chemical agents into tumors as an approach for cancer therapy has a longstanding history with William B. Coley’s efforts in the late 19 th century (Aznar et al, 2017; Marabelle et al, 2017). These agents include but are not limited to TLRs, RIG-I-like receptor (RLR) agonists, STING pathway modulators (Corrales et al, 2016; Li et al, 2017), and oncolytic viruses (Lawler et al, 2017).…”
Section: The Principles To Combine Other Therapeutics With Anti-pd Thmentioning
confidence: 99%
“…Intratumoral immunotherapy offers enhanced locoregional efficacy and reduced systemic toxicity by enabling high bioavailability of the agent at the injected tumor sites while limiting systemic exposure . Using tumor as a source of antigens expressed across multiple tumor clones, intratumoral immunotherapies aim to initiate local recruitment of immune cells into the tumor microenvironment and subsequently prime T cells for a systemic polyclonal antitumor response, potentially addressing intra‐ and intertumoral heterogeneity . Several intratumoral therapies with differing mechanisms of action have successfully entered clinical trials and shown promising results (Table ).…”
Section: Intratumoral Immunotherapiesmentioning
confidence: 99%
“…With this in mind, IT injection may enhance tumor-specific T cell responses while reducing significant systemic exposure to healthy tissue and off-target toxicities 43,44 . In addition, IT immunotherapy usually causes in situ priming of antitumor immunity, which may allow a patient's own tumor cells to be used as a therapeutic vaccine 43,44 . In our study, a lower dose of IT anti-PD-1 showed similar therapeutic effects as systemic delivery of a higher dose, and IT anti-CTLA-4 led to complete regression of most 4MOSC1 tumors that are primarily refractory to anti-PD-1.…”
Section: Discussionmentioning
confidence: 99%